Replacement of glutamine with the dipeptide derivative alanyl-glutamine enhances in vitro maturation of porcine oocytes and development of embryos. Issue 2 (May 2014) - Kim, Su Jin; Koo, Ok Jae; Kwon, Dae Kee; Kang, Jung Taek; Park, Sol Ji; Gomez, Ma Ninia; Atikuzzaman, Mohammad; Jang, Goo; Lee, Byeong-Chun
Summary The presence of glutamine (Gln) in in vitro maturation (IVM) and in vitro culture (IVC) medium is a more potent factor for improving porcine oocyte and embryo development than other amino acids. However Gln is inherently unstable and spontaneously breaks down into ammonia, and therefore interferes with proper development. To avoid this adverse effect, Gln was replaced in the present study with its stable dipeptide derivative alanyl-glutamine (Ala-Gln) and the effects of this replacement on porcine IVM and IVC were evaluated. Replacement of Gln with Ala-Gln during IVM did not improve nuclear maturation, however numbers of early cleaved embryos were significantly increased after activation. Blastocyst formation rates were also significantly improved by using Ala-Gln during IVM. Replacement of Gln with Ala-Gln during IVC significantly increased total cell numbers in blastocysts. Blastocyst formation rate was also significantly higher when Ala-Gln was used in both IVM and IVC. In conclusion, the use of Ala-Gln rather than Gln gives better results for development in both porcine IVM and IVC.